Home Advantage in Football: Exploring Its Effect on Individual Performance - Eduardo Chacón-Fernández; Gerard Brunsó-Costal; Abraham Duarte; Jesús Sánchez-Oro; Enrique Alonso-Pérez-Chao (Applied Sciences)
This study aimed to examine how playing at home affects individual football performance in the top five European leagues (LaLiga, Bundesliga, Serie A, Premier League, and Ligue 1) using offensive and defensive statistics. A secondary goal was to determine if these performance differences vary by field position. Offensive variables (season goals, assists, and key passes per game) and defensive variables (tackles, interceptions, and fouls per game) were analysed over eight seasons for 4337 players. Significant differences were found between home and away matches, particularly in goals (p < 0.001), assists (p < 0.001), and key passes (p < 0.001), all of which were higher at home. Defensive metrics like interceptions and fouls showed no significant differences, though tackles were higher away (p = 0.013). A positional analysis revealed that forwards and midfielders had significantly more goals (p < 0.001 for both) and assists (p = 0.008 for forwards, p = 0.029 for midfielders) at home. Defenders also had significantly more goals (p < 0.001) and assists (p < 0.001), while committing fewer fouls at home (p = 0.005). These findings suggest that playing at home significantly boosts individual performance, especially in offensive metrics. Coaches should adjust strategies based on if the match is at home or away, while considering individual player strengths and positions.